KONTRIBUSI KEKUATAN OTOT TUNGKAI TERHADAP KECEPATAN TENDANGAN SABIT PADA SISWA EKSTRAKURIKULER PENCAK SILAT SMA NEGERI 2 TAMBANG KABUPATEN KAMPAR - Dantes Harianja Harianja; Ramadi '; Slamet ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT : The identification of the problem revealed that one of the factors that influence the speed of the half-moon kick unsatisfactory not related to the leg muscle strength. The aim of this study to assess the contribution of the leg muscle strength at the speed of the crescent kick martial arts extracurricular student SMAN 2 Mining District Kampar.Jenis determine this research is correlational with a population of male students extracurricular Pencak Silat 2 Mine SMA Kampar regency of 20 people. This sampling technique is total sampling, thus reducing the number of samples in this study were 20 persons.From the analysis of the data is one of the data does not show a normal distribution, so that the correlation formula used is Lansiers correlation. From the calculation, it is known that there is a significant correlation between the variables x and y variables. based on the results of this study concluded that there is a significant correlation between the legs with a leg muscle rate half staircase, where the level of α = 00:05 obtained t = 2.97> t table = 2.10 The so Ho rejected and Ha accepted. Relationship variable X to Y vairabel be categorized and 0573 obtained count r> r table = 0.450. Keywords: leg muscle strength, speed crescent kick, martial arts